Exploring Branding and Packaging Design for Small Businesses in Parongpong - Pertiwi, Annisa Bela; Budiman, Budiman; Farid, Rudy; Firdaus, Muhammad (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
This paper discusses the results of a study and visual art creation conducted by the Graphic Design Study Program at Widyatama University, through a training project on branding and packaging design for small businesses in Parongpong District, West Bandung Regency. The project aims to explore and apply visual art principles in creating brand identity and packaging design that are both attractive and effective. This article describes how the Visual Communication Design lecturers and students provided training that integrates visual elements, graphics, narratives, and data related to the products of these small businesses into the branding and packaging design. The outcomes of this creative process are used by the business owners to enhance the competitiveness of their products in the market. Besides improving design skills, this project also contributes to the development of integrative attitudes, work ethics, and a spirit of cooperation, aligning with the mission of “Achieving Economic Independence of the Community as an Implementation of the Mental Revolution Movement.” Thus, the results of this study and creation are expected to serve as a long-term investment in knowledge and practical skills for these small business practitioners.